Transcriptional regulatory networks in Hepatitis C virus_induced hepatocellular carcinoma - Zahra, Marwa (AUC Knowledge Fountain, 2015)
HCV is an epidemic affecting an estimated 160 million individuals worldwide or approximately 2.35% of the world’s population.(1) This is partly because HCV exhibits high genetic variation which thereby characterizes each region with its own genetic prevalence. Therefore, understanding the transcriptional regulatory elements that influence the progression of liver disease in the presence of HCV infection is thereby crucial for diagnostic and therapeutic purposes. Systems biology provides a road map by which these elements may be easily identified. In this study 124 microarray samples were assessed in order to determine differentially expressed genes for 4 tissue types/conditions (normal, cirrhosis, cirrhosis HCC, and HCC). Differentially expressed genes were assessed for their functional clustering and those genes were annotated with their potential transcription factors and miRNAs. Transcriptional regulatory networks were constructed to visualize each pairwise comparison between the 4 tissue types/conditions. In this study that 12 transcription factors were found to have high expression patterns amongst all 6 pairwise comparisons and these transcription factors also provide insight the conditions of the liver as it progresses through hepatic cirrhosis, hepatic steatosis, and the induction of cancer. With the plethora of miRNAs that are found in the liver, each liver condition was found to have its own signature miRNA expression pattern. In the 6 pairwise comparisons 14 miRNAs were found to have high expression patterns in all 6 pairwise comparisons and their regulation in HCC was determined as well as their impact on cellular homeostasis. Based on the findings of this study and a systematic analysis of many studies it can be concluded that as the liver progresses from cirrhosis to steatosis and eventually becoming carcinomic there are specific transcription factors regulating this transition through each stage. Whereas the condition of the liver digresses, the down-regulation of miRNAs’ expression makes the transition of the liver through each pathological stage more apparent. Therefore, an understanding of the transcriptional regulatory attributes acts as a road map to provide interference strategies in order to target the stages in the progression of HCV induced HCC.